Intraventricular Flow Patterns in Patients Treated with Left Ventricular Assist Devices. Issue 1 (January 2021) - Rossini, Lorenzo; Braun, Oscar Ö.; Brambatti, Michela; Benito, Yolanda; Mizeracki, Adam; Miramontes, Marissa; Nguyen, Cathleen; Martinez-Legazpi, Pablo; Almeida, Shone; Kraushaar, Megan; Vu, Vi; May-Newman, Karen; et al.
Abstract : The success of left ventricular assist device (LVAD) therapy is hampered by complications such as thrombosis and bleeding. Understanding blood flow interactions between the heart and the LVAD might help optimize treatment and decrease complication rates. We hypothesized that LVADs modify shear stresses and blood transit in the left ventricle (LV) by changing flow patterns and that these changes can be characterized using 2D echo color Doppler velocimetry (echo-CDV). We used echo-CDV and custom postprocessing methods to map blood flow inside the LV in patients with ongoing LVAD support (Heartmate II, N = 7). We compared it to healthy controls (N = 20) and patients with dilated cardiomyopathy (DCM, N = 20). We also analyzed intraventricular flow changes during LVAD ramp tests (baseline ± 400 rpm). LVAD support reversed the increase in blood stasis associated with DCM, but it did not reduce intraventricular shear exposure. Within the narrow range studied, the ventricular flow was mostly insensitive to changes in pump speed. Patients with significant aortic insufficiency showed abnormalities in blood stasis and shear indices. Overall, this study suggests that noninvasive flow imaging could potentially be used in combination with standard clinical methods for adjusting LVAD settings to optimize flow transport and minimize stasis on an individual basis. Abstract : Supplemental Digital Content is available in the text.